Tornar-se artista : como se desenvolve o processo criativo? - Santos, Joana de Oliveira (2019)
The purpose of this document is to analyze and reflect on the etymological and historic definitions of the artist’s creative process in a specific area, the painting, which is inserted in the category of the plastic or visual arts. The questions and problems related to the topic of the “definition”, as well as the “stages” of the creative process are addressed from a social and historical point of view, with the intention of mapping and clarifying the mutations that occurred in the artistic practice as well as in the social and professional status of the artist. In that sense, some evolutions and historical mutations to the etymological definitions of keywords like “artificer” (a concept that goes back to the Middle Ages, referring to workmen or manual workers in a guild) or “artist” (which comes from the Renaissance, through the intellectual acknowledgement associated with the artistic practice) are analyzed by this document. Along with the social and historical study of the fundamental concepts and words for dealing with issues related to the creative process, of the painting artist, the artist’s workshop – as a witness to the stages that precede the work of art – is, in this context, one of the most important subjects of this analysis, through the mapping of the distinct creative workspaces from the Renaissance to the 21st Century. One of the objectives of this work is to clarify the dichotomy between “work of art” (the final product, which is socially, culturally, and economically overvalued) and the “creative process” (frequently brushed aside, neglected or forgotten either by the society, or by the Art History), being that, until the 20th Century, almost no records or reports about the artist’s creative process existed. On the other hand, this work tries to perceive how important “official” and “academic” education is for the consolidation of the “artist” status and for the artist’s recognition in social and professional environments, without, however, neglecting the self-taught route. Through its development, this work aimed to clarify the role of academic education in the development of the artist, finding out which methods and techniques were taught, its impact on the creative processes of each and every artist, and what influence academic institutions and schools of art had on the social and cultural acknowledgement of the painting artist. This work also sought to question the way in which the artist’s social environment contributes towards the acknowledgement, subsistence, and acceptance of the artist (and his work of art) by the general public, bringing to light some of the challenges, hardships and obstacles experienced during the creative process